Short-term and long-term exposure to combined elevated temperature and CO2 leads to differential growth, toxicity, and fatty acid profiles in the harmful dinoflagellate Karlodinium veneficum - Vidyarathna, Nayani K.; Smith, Laura E.; Miller, Katherine R.; Coyne, Kathryn J.; Cohen, Jonathan H.; Warner, Mark E. (Frontiers in Marine Science, 2024)
Ocean warming and acidification may significantly alter the distribution and intensity of harmful algal blooms as well as their effects on marine food webs. Estimating such effects rely, in part, on understanding the physiological response of individual algal species to controlled laboratory simulations of climate change conditions. Here we report the physiological response of the harmful dinoflagellate Karlodinium veneficum to the combined effects of elevated temperature and CO2 (29°C/1000 ppm CO2). We first examined these effects by comparing ambient control (25°C/441 ppm CO2) and elevated conditions under short-term ( 20 generations) growth. Next, we compared the short-term elevated condition to a longer-term ( 200 generations) growth scenario under the same elevated temperature and CO2. Under the short-term elevated conditions, K. veneficum growth declined, cell toxicity increased, and saturated and mono-unsaturated fatty acid (FA) composition varied significantly from ambient conditions. Meanwhile, after 200 generations of growth under elevated temperature and CO2, K. veneficum carbon assimilation, growth, and cell toxicity were significantly higher than the short-term elevated treatment. Further, while total saturated FA declined, essential fatty acids increased and likely represented an adaptive temporal response to long-term exposure to high temperature and CO2. Such shifts in FA profiles and cell toxicity may possibly alter K. veneficum nutritional quality as prey and its mixotrophic behavior, thereby affecting the energy and mass transfer through the marine food webs as well as bloom dynamics.